Limited Sanity in the Legislation of Russia and Europe - Yu. Zhilina, Natalia; S. Burtsev, Andrey; I. Lyakhova, Anzhelika; V. Savelieva, Irina; S. Shumilina, Oksana (International Journal of Criminology and Sociology, 2022)
This article presents the author’s analysis of the problem of limited sanity in the criminal law theory and practice of Russia and Europe. The author established that the problem of limited sanity, despite its long history, has not yet been developed in many countries, and that the boundaries of the concept of limited sanity are extremely vague and indefinite. However, the experience of some foreign countries in terms of ensuring security measures can be used in the Russian Federation.